Supplemental Stingless Bee Pollination in Fennel (Foeniculum vulgare Mill.): An Assessment of Impacts on Native Pollinators and Crop Yield - Layek, Ujjwal; Das, Alokesh; Karmakar, Prakash (Frontiers in Sustainable Food Systems, 2022)
The yield of many crops benefits from pollinating insects; thus, recently reported declines in pollinator abundance and diversity are concerning for global food production. The pollinator dependency and amount of yield enhancement may vary according to crop species and geographical location. Fennel (Foeniculum vulgare) is an important spice crop cultivated in Indian states. However, comprehensive knowledge about pollination demand and yield enhancement potential of managed bees is still unknown. Here, we conducted a replicated study in two successive years (2020 and 2021) in West Bengal by combining pollinator surveys, pollinator-exclusion experiments, and field manipulation on fennel, which quantifies the impacts of supplemental stingless bees (Tetragonula iridipennis) pollination on native pollinators and crop yield. The crop species attracted many insect species belonging to diverse groups. Among those, important native pollinators (based on ‘approximate pollination value’) were Apis cerana, Apis dorsata, Apis florea, and Oxybelus furculatus in open condition (i.e., without field manipulation and in the absence of managed bees). We derived the coefficient of pollination deficit (D) from the fruit set percentages in open and manually cross-pollination treatments. The obtained value (D = 0.18) implies that the crop species have pollen transfer limitations, resulting in retardation of crop yield. From field manipulation with managed stingless bee colonies, the abundance of visitors (especially stingless bee foragers) on fennel increased (without altering the foraging activity of other native pollinators), thereby fruit set and crop yield increased by about 14.89% and 19.31%, respectively. Native managed stingless bees had no negative impacts on other native unmanaged species and can be promoted as complementary and short-term means of boosting yields and improving agricultural sustainability.